Risk Factors Associated with antimicrobial Residues in the Milk Consumed in Nyala, South Darfur State, Sudan - Addoma, Fathalrhman E.; Abdelgadir, Atif E.; El Nahas, Ayman; El Zubeir, Ibtisam E. (Journal of Veterinary Medicine and Animal Production, 2021)
This study aimed to assess the contamination of milk by antimicrobial residues consumed in Nyala, South Darfur State, Sudan. A questionnaire and direct interviews with veterinarians at the veterinary pharmacies (n= 30) as well as with dairy farmers (n= 30) were carried out to determine the various risk factors associated with the presence of antimicrobial residues in milk. In addition, hundred milk samples were collected from dairy farms and sale points (n= 50, each) and were analyzed for antimicrobial residues by using Trisensor kit. The results revealed that 73.3% of the veterinarians believe that prescriptions are not necessary for drug dispensing, and that 43.3% of the veterinarians practice whole sale of antibiotics to dairy farm owners (P<0.001). However, 60% of the veterinarians guide the dairy farmers to be strict to antibiotic dose and 73.3% advise them about the way of administration. Moreover, only 56.7% of the veterinarians advise the dairy farmers about the importance of the withdrawal period, and 93.3% stated that most of the saleable drugs are broad spectrum antibiotics. On the other hand, 16.7% of the dairy farmers add antibacterial drugs to animal feed, with significant difference (P>0.01) between south and north Nyala. Fifty percent of dairy farmers administer antibiotics to healthy animal as prophylactic therapy, only 26.7% of them consult the veterinarians, 70% keep drug in the cattle yard and treat the animals by themselves, 73.3% do not apply the withdrawal period and non of them have balances to measure animal weight for suitable drug dosage. Furthermore, one hundred raw and heated milk samples (50 from dairy farms and 50 from sale points) collected by non- probability sampling method were screening for contamination with drugs residues using the Trisensor kit (detects simultaneously beta-lactams, tetracyclines and sulfonamides, in addition to the Triaminosensor kit (detects simultaneously gentamicin, streptomycin and neomycin). In both raw and heated milk, high contamination rates with tetracyclines (34% and 31%, respectively) and sulfonamides (31% and 29%, respectively) were detected, but with no significant difference (P>0.05). Contamination with beta-lactams was higher in milk samples collected from the sale points (37%) than in the samples from dairy farms (32%), but also the difference was not significant (P>0.05). While, neomycin was not detected, gentamicin was detected in 25% and 32% and streptomycin was found in 19% and 26% of raw and heated milk, respectively. In conclusion, contamination of milk by antimicrobial in Nyala indicates lack of proper and direct veterinary supervision in implementation of the legislations on the presence of veterinary drugs residues in milk in addition to the ignorance of withdrawal period of drugs.